Temperatism. - Foster, Carrie, (Human resource management and organizational behavior collection., 2018)
This book isn't intended to have all the answers, but explores the question 'How much wealth is enough?' Examining the idea that the capitalist profit agenda is not benefiting society or democracy, Temperatism investigates whether there is an alternative to the profit agenda currently followed by organizations and society. If growth and profit are an important part of the equation, then the question that arises is "Important for what purpose?" What follows is a proposition of an alternative agenda of doing good and the introduction of a new business framework--temperatism.